Speculative fictions : contemporary Canadian novelists and the writing of history - Wyile, Herb, 1961- (McGill-Queen's University Press, 2002)
"Herb Wyile provides a comparative analysis of the historical concerns and textual strategies of twenty novels published since the appearance of Rudy Wiebe's groundbreaking The Temptations of Big Bear in 1973. Drawing on the work of theorists and critics such as Mikhail Bakhtin, Fredric Jameson, and Linda Hutcheon, Speculative Fictions examines the nature of these novels' engagement with Canadian history, historiography, and the writing of historical fiction. Wyile concludes that the writing of history in English-Canadian fiction over the last thirty years makes a substantial contribution to a revisioning of history and to a postcolonial renegotiation of Canadian society"--Jacket